ANTI-INFLAMMATORY, ANALGESIC AND COGNITIVE ENHANCER PLANTS PRESENT IN BANGLADESH: A STUDY REVIEW - Uddin, Sultan Sala; Islam, Md. Shahidul (Universal Journal of Pharmaceutical Research, 2020)
In present scenario the exploit of conventional medicine is enlarging to newer prospects in addition to plants still stay as the original source of the structurally significant compounds that guide to the expansion of the innovative drugs. Recently Bangladesh has concerning forty five thousands plant variety among which therapeutic assets has been treated to the several thousands. The conventional Bangladeshi system of the medicine, Ayurveda reveals the exercise of the plants in treatment of the various diseases. The ethnobotanical investigation done in the most recent few decades have revealed cognitive, anti-inflammatory as well as analgesic actions of the plants mentioned in the conventional literature. Numerous herbal groundings are being stipulated as the anti-inflammatory, cognitive as well as analgesic in traditional literature. The research for innovative anti-inflammatory, cognitive and analgesic agents from enormous array of the medicinal plant sources is escalating. This reviews such type of the plant species in addition to their products which have demonstrated experimental and clinical anti-inflammatory and also analgesic, cognitive actions, the possible method of the action in addition to their therapeutic value. Several of the significant taxa which are originated efficient as cognitive, anti-inflammatory and analgesic agents such as Callophyllum inophyllum L, Ananas comosus (L.) Merr., Calotropis gigantea (L.) R.Br., Camellia sinensis (L.) Kuntz., Calotropis procera (Ak.) R.Br., Cannabis sativa L., Curcuma longa L., Kalanchoe crenata Andr., Spillanthes acmella Murr, Mangifera indica L., Ricinus communis Linn., Sida cordifolia L., Zingiber officinale Roscoe, Ginkgo biloba , Zizyphus jujube, Emblica Officinalis, Cocos nucifera, Celastrus paniculatus. Here these plants species have shown contrasting degrees of cognitive, anti-inflammatory as well as analgesic activities. Peer Review History: Received: 10 August 2020; Revised: 13 September; Accepted: 24 October; Available online: 15 November 2020 Academic Editor: Dr. Tamer Elhabibi , Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Reviewer(s) detail: Dr. Marwa A. A. Fayed , University of Sadat City, Egypt, maafayed@gmail.com Dr. Hatem Sameir Abbas , Al-Azhar University, Egypt, hsam8406@yahoo.com